Challenges Towards Digitalization for Leadership in Pakistan (Financial Industry) - Rana, Mohammad Afzal (Digital Repository of Theses - SSBM Geneva, 2025)
The Pakistani financial industry has been observing a major lash due to current economic instability. The economic instability scandal has affected nations globally and has had an extremely negative impact on the country due to its debt and taking additional debts from the IMF, World Bank, and other countries. The specific problem within financial industry in Pakistan concerns the lack of innovative leadership interventions to achieve efficiency, accessibility, and competitiveness. There are also certain limitations of infrastructure which challenge the intention to digitalized the financial sector in Pakistan. The purpose of this single qualitative study was to achieve a deeper understanding on how innovative leadership interventions are planned, aligned and implemented in the financial industry in Pakistan and how these interventions may contribute to efficiency, accessibility, and competitiveness. The study used the Theory of transformational leadership as the theoretical framework and was based on semi-structured interviews with eight (N=8) participants from five financial institutions in Pakistan. The financial institutions and participants were purposively selected. The study findings clearly indicated that the strategic leadership plays a very important role in successfully aligning, planning and implementing the innovative interventions in the financial sector of Pakistan, as well as the organizational goals with technological advancements and adoption of digitalized solutions. In addition, it indicated that the inclusion of smart technology from Industry 4.0 strengthens the relationship between inventive performance and organizational sustainability. Finaly, the findings indicated that innovative interventions of leadership improve efficiency, accessibility, and competitiveness in the financial sector of Pakistan. The implication of this study highlights the positive societal impact of sustainable leadership practices, including increased profits, job creation in Pakistan's financial sector, and a reduction in the country's unemployment rate. This study contributed to the field of business and management by filling the research gap in terms of trying to understand how innovative leadership interventions can be used to achieve efficiency, accessibility, and competitiveness. Recommandations for future research include exploring similar themes in other industries, geographic regions, or cultural contexts to deepen understanding of how leadership can drive digital transformation in varying environments. Keywords: Innovative transformational Leadership, Digital Transformation, Financial Sector in Pakistan, Organizational Efficiency